Preparation method of bio-based smoke-suppressing, toxicity-reducing and flame-retardant coating

By self-assembling bio-based smoke-resistance attenuated flame retardant coatings on the surface of wood materials and polyurethane foamed materials, the problems of flammability and large flue gas release are solved, and efficient flame retardant performance and environmental protection are achieved, improving the quality of the improvement of the quality of the fire retardant coating. Fire safety and materials application areas.

CN119192913AActive Publication Date: 2024-12-27BEIJING FORESTRY UNIVERSITY

Patent Information

Application Number
CN202411334970.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

Wood materials and polyurethane foaming materials are flammable and release a large amount of flue gas and carbon monoxide in fires, which poses a fire safety hazard. Traditional flame retardants have poor environmental protection, and the N-P-based flame retardants release a large amount of flue gas during the flame retardant process.

Method used

Using bio-based flame retardant, by preparing flame retardant molecular sieve and bio-based smoke inhibition attenuated flame retardant coating, layers of self-assemble on the surface of the substrate, combining chitosan, hydrolyzed collagen and phytic acid to reduce flue gas and carbon monoxide The release amount improves the flame retardant performance of the substrate.

Benefits of technology

It significantly improves the flame retardant performance of the substrate, reduces the release of flue gas and carbon monoxide, enhances the safety of the fire site, and has the characteristics of environmental protection, low cost and high efficiency, expanding the application field of materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a bio-based smoke-suppressing, toxicity-reducing and flame-retardant coating, and relates to the field of flame retardance of wood materials and polyurethane foam materials. A wood material and a polyurethane foaming material are used as matrixes, a hydrolyzed collagen aqueous solution and a molecular sieve are added into a phytic acid aqueous solution to obtain a PDF solution, and the matrixes are sequentially soaked in CS and PDF solutions to obtain the bio-based flame-retardant coating. The preparation method can be widely applied to wood materials, polyurethane foam materials and the like. The method provided by the invention not only can greatly improve the flame retardant property of the matrix material and reduce the release amount of smoke and carbon monoxide, but also has the characteristics of high transparency, environmental friendliness, simplicity and convenience in operation, low cost and the like, and has the application prospect of large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a bio-based smoke suppression and toxicity reduction flame retardant coating, and in particular to a method for preparing a halogen-free environmentally friendly flame retardant coating. Technical Background

[0002] Wood materials and polyurethane foam materials are two lightweight materials with a large amount of usage at present. They have the advantages of high strength-to-weight ratio and low price. They are widely used in furniture manufacturing, construction and packaging fields. However, wood materials and polyurethane foam materials without flame retardant treatment are very flammable. The limiting oxygen index of wood is only about 22%, while the limiting oxygen index of polyurethane foam materials is only 17-18%. Under such conditions with fire safety hazards, once a fire occurs, it may cause irreparable huge losses. In the process of a fire, the combustion of combustibles will produce a large amount of smoke particles and carbon monoxide gas. Smoke particles will not only interfere with the vision of escapees, but also affect the inhalation of too much smoke and carbon monoxide, causing escapees to faint, reducing the success rate of escape. Therefore, in view of the disadvantages of flammable wood materials and polyurethane foam materials and the release of toxic smoke, it is necessary to adopt necessary flame retardant modification methods to improve the flame retardant properties of wood materials and reduce the amount of smoke released.

[0003] In order to eliminate the threat of fire, the method of impregnating or coating with flame retardants to improve the flame retardant properties of the substrate is widely used. Commonly used flame retardants include metal hydroxides, borides, ammonium polyphosphate and other materials. Although these materials have good flame retardant effects, they are not environmentally friendly and have potential hazards to humans and the environment when used for a long time. Developing more environmentally friendly and efficient flame retardant strategies remains a challenging task. Some materials extracted from natural plants and animals, such as chitosan (CS), phytic acid (PA), tannic acid, sodium alginate, animal and plant proteins and other bio-based materials, can not only overcome the problem of poor environmental protection of traditional flame retardants, but also provide rich flame retardant elements such as N and P, and have the potential to achieve high-performance flame retardancy. However, NP-based flame retardants have the disadvantage of large smoke release during the flame retardant process. In order to reduce the smoke release during the flame retardant process, molecular sieves are used to adsorb the smoke, enhance the strength of the substrate carbon layer, and reduce the smoke release.

[0004] The present invention uses bio-based flame retardant as a main component, promotes the improvement of flame retardant performance of the substrate, reduces the emission of smoke and carbon monoxide, and reduces the risk of fire. Summary of the invention

[0005] (1) Preparation of flame-retardant molecular sieve: A certain amount of tetrapropylammonium hydroxide, seed liquid, tetraethyl orthosilicate and deionized water are sequentially hydrothermally reacted at a certain temperature for a certain time, which is recorded as solution A. A certain amount of aluminum-containing compound is added to a certain amount of deionized water and stirred for a certain time, which is recorded as solution B. A certain amount of growth regulator is added to a certain amount of deionized water and stirred for a certain time, which is recorded as solution C. Solution B is added to solution A and stirred evenly, and then solution C is added and stirred evenly to obtain a mixed solution D. Solution D is transferred to a reactor and hydrothermally reacted at a certain temperature for a certain time to obtain a white solid. After drying in an oven until there is no obvious moisture, it is calcined in a muffle furnace at a certain temperature for a certain time to obtain a flame-retardant molecular sieve.

[0006] (2) The bio-based smoke suppression and toxic reduction flame retardant coating is attached to the surface of the substrate: a certain amount of chitosan is added to a certain amount of deionized water, a certain amount of glacial acetic acid is added, and the chitosan is stirred to fully dissolve. The substrate is completely immersed in the chitosan solution for a certain period of time. After the sample is taken out, the sample is dried at a certain temperature until there is no obvious moisture on the surface to obtain sample CS. A certain amount of hydrolyzed collagen and a certain amount of molecular sieve are completely dissolved in deionized water, and then a certain amount of phytic acid solution is added and mixed evenly to obtain a solution PDF. The sample CS is immersed in the above PDF solution for a certain period of time and then dried at a certain temperature until there is no obvious moisture on the surface to obtain the substrate treated with the bio-based smoke suppression and toxic reduction flame retardant coating.

[0007] Preferably, the seed solution in step (1) is mixed in a ratio of ethyl orthosilicate: tetrapropylammonium hydroxide (20-30) g: (15-20) g, and the stirring temperature is 35-45° C. and the stirring time is 0.5-2 h. The uniformly stirred mixture is then transferred to a high-pressure reactor at a temperature of 60-70° C. and a heating time of 24-96 h to synthesize the seed solution.

[0008] Preferably, the addition ratio of tetrapropylammonium hydroxide, seed solution, tetraethyl orthosilicate and water in solution A of step (1) is (14-16) g: (10-12) g: (30-40) g: (45-60) g.

[0009] Preferably, the aluminum-containing compound in step (1) is one or a mixture of aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum acetate, and the amount of the aluminum-containing compound added is 0.4-0.6 g. The growth regulator is ethanol, ammonium fluoride, sodium fluoride, and urea, and the amount of addition is 5-8 g.

[0010] Preferably, the time of step (1) in the reaction kettle is 12-24 hours, and the reaction temperature is 160-190° C. The calcination temperature of the muffle furnace is 400-600° C., and the calcination time is 3-6 hours.

[0011] Preferably, the deionized water content of solution B and solution C in step (1) is 60-100 g, and the stirring time is 0.5-5 h.

[0012] Preferably, the substrate in step (2) is wood, polyurethane foam, particle board, fiberboard, plywood, blockboard, veneer, etc.

[0013] Preferably, the molecular sieve in step (2) can be prepared by the method of step (1), or can be other types of molecular sieves available on the market.

[0014] Preferably, the amount of chitosan added in step (2) is 2-4 g, the mass of deionized water is 200-350 g, the amount of glacial acetic acid added is 1-3 mL, the mass fraction of phytic acid solution is 30-50%, the mass of phytic acid solution is 200-300 g, the amount of hydrolyzed collagen added is 5-10 g, and the amount of molecular sieve added is 0.3-1 g. The immersion time is 1-10 min, and the drying temperature is 50-60 ° C. DETAILED DESCRIPTION

[0015] In order to better illustrate the technical means and preparation process of the present invention, the present invention is explained below in conjunction with specific implementation cases.

[0016] Embodiment 1:

[0017] (1) 56 g of tetraethyl orthosilicate (TEOS) and 40 g of tetrapropylammonium hydroxide (TPAOH) were stirred at 35°C for 6 h, and then the temperature of the solution was raised to 45°C and heated for 1 h to remove the generated ethanol. The stirred mixture was then transferred to a high-pressure reactor at 70°C for 24 h to obtain a seed solution.

[0018] 4.4 g of TPAOH, 2.5 g of seed solution, 8 g of TEOS and 12 g of water were stirred at 35 °C for 1 h, which was recorded as solution A. 0.1 g of AlCl 3 Add 20g of deionized water and stir for a certain time, record it as solution B. Add 1g NH4F to 20g of deionized water and stir for 30min, record it as solution C. Add solution B to solution A and stir evenly, then add solution C and stir evenly to obtain mixed solution D, transfer solution D to a reactor, hydrothermally react at 170℃ for 12h to obtain a paste-like white solid, dry it in an oven at 80℃ until there is no obvious moisture, and calcine it in a muffle furnace at 550℃ for 2h to obtain a molecular sieve.

[0019] (2) Add 4 g CS to 300 g deionized water, add 2 mL of glacial acetic acid, and stir vigorously to fully dissolve CS. Immerse the poplar wood completely in the CS solution for 2 min, take out the sample and dry it at 60 ° C until there is no obvious moisture on the surface to obtain sample CS. Dissolve 20 g hydrolyzed collagen and 0.5 g molecular sieve completely in 40 g deionized water, then add to 160 g 50 wt% PA solution and mix well to obtain solution PDF. Immerse sample CS in the above PDF solution for 2 min and then dry it at 60 ° C until there is no obvious moisture on the surface to obtain sample CPDF.

[0020] The LOI of sample CPDF is 29.5%, which is 32.9% higher than that of untreated poplar wood. The pHRR, THR, TSP, etc. are decreased by 70.8%, 74.6%, and 52.7% respectively compared with untreated poplar wood.

[0021] Embodiment 2:

[0022] (1) 56 g of TEOS and 40 g of TPAOH were stirred at 35 °C for 6 h, and then the temperature of the solution was raised to 45 °C and heated for 1 h to remove the generated ethanol. The stirred mixture was then transferred to an autoclave at 70 °C for 24 h to obtain a seed solution.

[0023] 4.4 g of TPAOH, 2.5 g of seed solution, 8 g of TEOS and 12 g of water were stirred at 35 °C for 1 h, which was recorded as solution A. 0.1 g of AlCl 3 Add 20 g of deionized water and stir for a certain period of time, which is recorded as solution B. 4 F was added and 20 g of deionized water was stirred for 30 min, which was recorded as solution C. Solution B was added to solution A and stirred evenly, and then solution C was added and stirred evenly to obtain a mixed solution D, which was transferred to a reactor and subjected to hydrothermal reaction at 170°C for 12 h to obtain a paste-like white solid, which was dried in an oven at 80°C until there was no obvious moisture, and then calcined in a muffle furnace at 550°C for 2 h to obtain a molecular sieve.

[0024] (2) Add 4 g CS to 300 g deionized water, add 2 mL glacial acetic acid, and stir vigorously to fully dissolve CS. Immerse the poplar wood completely in the CS solution for 2 min, take out the sample and dry it at 60 ° C until there is no obvious moisture on the surface to obtain sample CS. Dissolve 20 g hydrolyzed collagen completely in 40 g deionized water, without adding molecular sieves, and then add it to 160 g 50 wt% PA solution and mix well to obtain solution PD. Immerse sample CS in the above PD solution for 2 min and then dry it at 60 ° C until there is no obvious moisture on the surface to obtain sample CPD.

[0025] The LOI of sample CPD is 29.0%, which is 30.6% higher than that of untreated poplar wood, and the pHRR is 30.7% lower than that of untreated poplar wood.

[0026] Example 3

[0027] 4 g of CS was added to 300 g of deionized water, and 2 mL of glacial acetic acid was added, and the mixture was stirred vigorously to fully dissolve the CS. The poplar wood was completely immersed in the CS solution for 2 min, and the sample was taken out and dried at 60 ° C until there was no obvious moisture on the surface to obtain the sample CS. 20 g of hydrolyzed collagen and 0.5 g of commercially available ZSM-5 molecular sieve were completely dissolved in 40 g of deionized water, and then added to 160 g of 50 wt% PA solution and mixed evenly to obtain a solution PDF. The sample CS was immersed in the above PDF solution for 2 min and then dried at 60 ° C until there was no obvious moisture on the surface to obtain the sample CPDS.

[0028] The LOI of the sample CPDS is 29.1%, which is 31.1% higher than that of the unfire-retardant poplar wood.

[0029] In summary, the present invention obtains a flame retardant coating by self-assembling layer by layer on the surface of a flammable substrate. Due to the high transparency, it not only does not affect the texture characteristics of the substrate itself, but also has a very high flame retardant and smoke suppression performance, which makes the substrate have a very large advantage at the fire scene, and also has a very good effect in suppressing CO release, which can provide favorable conditions for escape. The present invention has the advantages of low cost, strong operability, environmental friendliness and large-scale preparation, expands the application field of wood materials and polyurethane foam materials, and provides a new perspective for the functional utilization of wood materials and polyurethane foam materials.

[0030] The above describes the specific embodiments of the present invention. However, professionals in the field should understand that the above embodiments are intended to illustrate the principles of the invention, and the present invention is not limited to the specific embodiments. Any technical changes to the present invention are within the scope of protection of the present invention without departing from the technology of the present invention.

Claims

1. A method for preparing a bio-based smoke suppression and toxicity reduction flame retardant coating, comprising the following steps: (1) Preparation of flame retardant molecular sieve: a certain amount of tetrapropylammonium hydroxide, seed liquid, tetraethyl orthosilicate and deionized water are sequentially hydrothermally reacted at a certain temperature for a certain time, which is recorded as solution A; a certain amount of aluminum-containing compound is added to a certain amount of deionized water and stirred for a certain time, which is recorded as solution B; a certain amount of growth regulator is added to a certain amount of deionized water and stirred for a certain time, which is recorded as solution C; solution B is added to solution A and stirred evenly, and then solution C is added and stirred evenly to obtain a mixed solution D, which is transferred to a reactor and hydrothermally reacted at a certain temperature for a certain time to obtain a white solid, which is dried in an oven until there is no obvious moisture, and then calcined in a muffle furnace at a certain temperature for a certain time to obtain a flame retardant molecular sieve; (2) Attachment of the bio-based smoke suppression and toxic reduction flame retardant coating on the surface of the substrate: add a certain amount of chitosan to a certain amount of deionized water, add a certain amount of glacial acetic acid, and stir to fully dissolve the chitosan; immerse the substrate completely in the chitosan solution for a certain period of time, take out the sample and dry the sample at a certain temperature until there is no obvious moisture on the surface to obtain sample CS; completely dissolve a certain amount of hydrolyzed collagen and a certain amount of molecular sieve in deionized water, then add a certain amount of phytic acid solution and mix evenly to obtain solution PDF, immerse sample CS in the above PDF solution for a certain period of time and then dry it at a certain temperature until there is no obvious moisture on the surface to obtain the substrate treated with the bio-based smoke suppression and toxic reduction flame retardant coating; The seed solution in step (1) is mixed in a ratio of ethyl orthosilicate to tetrapropylammonium hydroxide (20-30) g: (15-20) g, and the stirring temperature is 25-45° C. and the stirring time is 0.5-24 h; then the stirred mixture is transferred to a high-pressure reactor, the temperature is 60-70° C., and the heating time is 24-168 h to synthesize the seed solution; The addition ratio of tetrapropylammonium hydroxide, seed solution, tetraethyl orthosilicate and water in solution A of step (1) is (14-16) g: (10-12) g: (30-40) g: (45-60) g; The aluminum-containing compound in step (1) is one or a mixture of aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum acetate, and the addition amount of the aluminum-containing compound is 0.4-0.6 g. The growth regulator is one or a mixture of ethanol, ammonium fluoride, sodium fluoride, and urea, and the addition amount is 5-8 g; The time of step (1) in the reactor is 6-48 hours, and the reaction temperature is 140-200° C.; the calcination temperature in the muffle furnace is 400-800° C., and the calcination time is 1-8 hours; In step (1), the deionized water content of solution B and solution C is 60-100 g, and the stirring time is 0.5-5 h; The substrate in step (2) is wood, polyurethane foam, particle board, fiberboard, plywood, blockboard, etc.; The molecular sieve in step (2) may be prepared in the manner of step (1), or may be other types of molecular sieves available on the market; The amount of chitosan added in step (2) is 2-4 g, the mass of deionized water is 200-350 g, the amount of glacial acetic acid added is 1-5 mL; the mass fraction of the phytic acid solution is 10-70%; the mass of the phytic acid solution is 200-500 g, the amount of hydrolyzed collagen added is 5-30 g, and the amount of molecular sieve added is 0.3-3 g; The immersion time is 1-600 minutes, and the drying temperature is 50-60°C.

Citation Information

Patent Citations

  • Special auxiliary agent for enhancing hardness of polyurethane sponge as well as processing device and process

    CN117247605A

  • Decomposable composite fire-retardant sheet and method for utilizing waste thereof

    JP2003211592A

  • Fire retardant nonwoven material and process for manufacture

    US20080050565A1

Cited By

  • Roller shutter fabric and production process thereof

    CN120925331A

  • A roller blind fabric and a production process thereof

    CN120925331B